Optimal household energy management based on smart residential energy hub considering uncertain behaviors. (15th March 2020) - Lu, Qing; Lü, Shuaikang; Leng, Yajun; Zhang, Zhixin
Abstracts: Nowadays, confronting with the emerging energy crisis and environmental pressure, multi energy integrating technologies are considered as effective patterns to augment the renewable energy consumption and improve energy efficiency in the context of energy transformation and reform. In this paper, household energy management based on smart residential energy hub (SREH) whose inputs include electricity and natural gas is designed for modern households. Relevant energy-using equipment models as well as control strategies are proposed through the physical characteristics and household users' preferences, respectively. A multi-objective optimization problem is formulated to allocate energy supply in the SREH, and provide scheduling schemes for energy-using equipment beside the classified ordinary appliances. Six kinds of uncertain behaviors are modelled in comfort deviation as sub-objective. The overall objective of the problem is to minimize both the energy consumption expense and comfort deviation. Then, four cases studies are presented to verify the effectiveness of the proposed model, where both of the sub-objective value improves as a result. Finally, the robustness of the model are illustrated with actual behaviors of household users. The sensibility analysis of departure time distribution, weighing factors and number of uncertain scenarios are carried out to optimize the decision configuration. Highlights: A household energy management system based on smart residential energy hub. Energy-using equipment are classified through equivalent physical parameters. Control strategies with preference in energy-using equipment are available. Household users' uncertain behaviors are formulated as energy consumption deviation. Multi-objective optimization refers to energy consumption expense and comfort.